Preparation method and application of catalytic ozonation composite catalyst
Clay granules were prepared by using clay and MnSO4 solutions, and combined with coprecipitation-redoxification method to prepare composite powder catalysts, MFTA@ clay ozone catalyst was prepared, which solved the problems of poor stability and high cost of existing heterogeneous catalysts, and achieved efficient and stable water treatment effect.
Patent Information
- Application Number
- CN202510087146.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing heterophase ozone catalysts have problems such as easy shedding of active components, short service life, poor stability and high preparation costs, which limits the application of catalytic ozone oxidation technology in the field of water treatment.
Ceramic granules were prepared by clay and MnSO4 solution, and a composite powder catalyst was prepared by co-precipitation-redox method. Finally, it was mixed with the granules and roasted to prepare the MFTA@ceramic ozone catalyst.
The rate and stability of the catalytic oxidation reaction are improved, the catalytic oxidation efficiency of difficult-to-degrade organic matter is enhanced, and it is more than 45% higher than ozone oxidation alone, saving operating costs and avoiding secondary pollution during catalytic oxidation.
Smart Images

Figure CN119869548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method and application of an ozone catalytic oxidation composite catalyst. Background Art
[0002] Whether it is the deep treatment of industrial wastewater or the treatment of domestic sewage, upgrading and transformation requires efficient and feasible treatment technology. As an important branch of advanced oxidation technology, heterogeneous catalytic ozone oxidation technology is one of the effective means. Ozone catalytic technology uses the catalytic action of the catalyst to promote the rapid decomposition of ozone to produce hydroxyl free radicals with strong oxidizing properties (redox potential reaches 2.8eV). Hydroxyl free radicals are non-selective to pollutants and can quickly and efficiently remove organic matter in water without causing secondary pollution. It is currently a hot topic of research.
[0003] However, most of the current heterogeneous ozone catalysts have the disadvantages of easy shedding of active components, short service life, poor stability, and high preparation cost, which seriously limits the application of catalytic ozone oxidation technology in the field of water treatment. Therefore, it is of great practical significance to develop an ozone catalyst with high catalytic activity, low price, high mechanical strength and good stability. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of an ozone catalytic oxidation composite catalyst, aiming to solve the problem of poor stability of existing multi-phase ozone catalysts.
[0005] To achieve the above object, in a first aspect, the present invention provides a method for preparing an ozone catalytic oxidation composite catalyst, comprising the following steps: Preparation of ceramsite using clay and MnSO4 solution; The composite powder catalyst was prepared by coprecipitation-oxidation-reduction method; The ceramsite and the composite powder catalyst are mixed and calcined to obtain the MFTA@ceramsite ozone catalyst.
[0006] Among them, in “preparing ceramsite using clay and MnSO4 solution”, the MnSO4 is 0.01~0.5MMnSO4 solution, and the particle size of the ceramsite is 5~7mm.
[0007] Among them, in the "preparation of a composite powder catalyst by a coprecipitation-oxidation-reduction method", the composite powder catalyst is composed of at least two (MFTA) of the four metal oxides of Mn, Fe, Ti, and Al.
[0008] Among them, in “preparing a composite powder catalyst by a coprecipitation-oxidation-reduction method”, the following steps are included: The Mn component in the MFTA catalyst was prepared by a redox method; KMnO4 solution was dripped into MnSO4 solution at 60-90°C, and after the dripping was completed, the reaction was continued for 6-12 hours and the aging was continued for 6-8 hours; Dissolve TiOSO4·H2SO4·H2O in water, stir the solution until it becomes colorless and transparent, then add Fe(NO3)3·9H2O and Al(NO3)3·9H2O in sequence, continue stirring for 2-4 hours, then add the Mn component prepared by the redox method, stir evenly, slowly drop NaOH to adjust the pH to neutral, continue stirring for 6-8 hours after the pH value stabilizes, and stand at 60-90°C for aging to obtain a solid precipitate; The solid precipitate was washed with water, filtered and dried in an oven for 12 hours to obtain a composite catalyst, which was then ground into powder.
[0009] Among them, in “mixing ceramsite and composite powder catalyst and then calcining to obtain MFTA@ceramsite ozone catalyst”, the mixing ratio of the composite powder catalyst and the ceramsite is 8~10:1.
[0010] In a second aspect, an application of an ozone catalytic oxidation composite catalyst is provided. Based on the preparation method of the ozone catalytic oxidation composite catalyst described in the first aspect, the MFTA@ceramsite ozone catalyst is applied to water treatment.
[0011] The invention discloses a method for preparing a composite catalyst for ozone catalytic oxidation, comprising the following steps: preparing ceramsite using clay and MnSO4 solution; preparing a composite powder catalyst by a coprecipitation-oxidation-reduction method; mixing the ceramsite and the composite powder catalyst and then calcining to obtain an MFTA@ceramsite ozone catalyst. The invention selects ceramsite as a carrier, which is simple to prepare, low in price, and has a stable structure, which is conducive to the uniform loading of active components and improves the rate of catalytic oxidation reaction. The ceramsite-loaded Fe, Mn, Al, and Ti catalysts are prepared by a spherical granulation method, and the active components are firmly loaded, evenly distributed, and have high dispersion, and the preparation process is simple, reproducible, and energy consumption is low. The selected carrier and active components are common commercially available materials, and the preparation cost is low. The prepared catalyst can generate more hydroxyl radicals, improve the oxidation efficiency and utilization rate of ozone, greatly improve the catalytic oxidation efficiency of refractory organic matter, and is more than 45% higher than that of single ozone oxidation, saving operating costs. At the same time, after repeated use, it is found that the active components are firmly attached and not easy to lose, thereby avoiding secondary pollution during the catalytic oxidation process. Thus, the problem of poor stability of existing multi-phase ozone catalysts is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 The present invention provides a flow chart of a method for preparing an ozone catalytic oxidation composite catalyst.
[0014] Figure 2 The present invention is a flow chart of preparing composite powder catalyst by coprecipitation-redox method. DETAILED DESCRIPTION
[0015] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0016] See also Figure 1 to Figure 2 In a first aspect, the present invention provides a method for preparing an ozone catalytic oxidation composite catalyst, comprising the following steps: S1 uses clay and MnSO4 solution to prepare ceramsite; The MnSO4 is a 0.01-0.5MMnSO4 solution, and the particle size of the ceramsite is 5-7mm.
[0017] Specifically, clay is placed in a planetary granulator and sprayed with 0.01-0.5M MnSO4 solution. The powder particles agglomerate under the action of liquid bridge and capillary force to form micro-nuclei. Under the friction and rolling impact generated by the rotation of the container, they continue to rotate and grow in the powder layer, and finally become spherical particles of a certain size. Ceramic particles with a particle size of 5-7 mm are selected for the subsequent preparation of multi-phase ozone catalysts.
[0018] S2 uses coprecipitation-redox method to prepare composite powder catalyst; The composite powder catalyst is composed of at least two (MFTA) of four metal oxides of Mn, Fe, Ti and Al.
[0019] S21 uses a redox method to prepare the Mn component in the MFTA catalyst; KMnO4 solution is dripped into MnSO4 solution at 60-90°C, and after the dripping is completed, the reaction is continued for 6-12 hours and the aging is carried out for 6-8 hours; Specifically, the Mn component in the MFTA catalyst is prepared by a redox method. A certain concentration of KMnO4 solution is slowly dripped into a MnSO4 solution at 60-90°C, and after the dripping is completed, the reaction is continued for 6-12 hours and the aging is carried out for 6-8 hours.
[0020] S22 Dissolve TiOSO4·H2SO4·H2O in water, stir the solution until it becomes colorless and transparent, add Fe(NO3)3·9H2O and Al(NO3)3·9H2O in sequence, continue stirring for 2-4 hours, then add the Mn component prepared by the redox method, stir evenly, slowly drop NaOH to adjust the pH to neutral, continue stirring for 6-8 hours after the pH value stabilizes, and let stand at 60-90°C for aging to obtain a solid precipitate; Specifically, the three components of Fe-Ti-Al in the MFTA catalyst were prepared by coprecipitation method. TiOSO4·H2SO4·H2O was dissolved in water, and Fe(NO3)3·9H2O and Al(NO3)3·9H2O were added in sequence after stirring the solution until it became colorless and transparent. After stirring for 2-4 hours, the Mn component prepared by the redox method was added, and after stirring evenly, NaOH was slowly dripped in to adjust the pH to neutral. After the pH value stabilized, stirring was continued for 6-8 hours, and the solution was allowed to stand at 60-90°C for aging.
[0021] S23: Wash the solid precipitate with water, filter it, and then dry it in an oven for 12 hours to obtain a composite catalyst, which is then ground into powder.
[0022] Specifically, after aging, the solid precipitate is washed with water and filtered to remove excess metal ions and acid ions, and then the solid precipitate is placed in an oven to dry for 12 hours. The dried composite catalyst is carefully ground into powder in an agate mortar for later use.
[0023] S3: Mixing the ceramsite and the composite powder catalyst and then calcining them to obtain the MFTA@ceramsite ozone catalyst.
[0024] The mixing ratio of the composite powder catalyst to the ceramsite is 8-10:1.
[0025] Specifically, the ceramsite prepared in step 1 is placed in a granulator and a small amount of MnSO4 solution is sprayed on the surface to make the surface of the ceramsite wet and sticky, the composite catalyst powder prepared in step 2 is mixed with clay in a mass ratio of 8 to 10:1, and a small amount and multiple additions are made in the granulator to evenly coat the surface of the ceramsite. Finally, the ceramsite coated with powder is placed in a muffle furnace for calcination to obtain the MFTA@ceramsite ozone catalyst.
[0026] Example 1 Place the ceramsite prepared in step 1 in a granulator and spray a small amount of MnSO4 solution on the surface. Mix the composite catalyst powder prepared in step 2 with clay in a mass ratio of 8-10:1, add it in small amounts and multiple times in the granulator to evenly coat the surface of the ceramsite, sieve out small balls of 5-7 mm, place them in a muffle furnace and roast them at 700-1200°C for 4 hours to obtain a spherical catalyst.
[0027] In the spherical catalyst prepared in this embodiment, the total loading amount of the active component oxide is 5-20%.
[0028] Catalytic performance test: The spherical catalyst prepared in this embodiment was used to treat the coking wastewater with ozone catalytic oxidation. The coking wastewater came from the secondary effluent of a coal chemical enterprise in Shanxi Province and had been subjected to multiphase Fenton oxidation treatment. The quality of the wastewater is shown in Table 1. The reaction device was a glass column (inner diameter 10 cm, height 1 m), the O3 gas flow rate at the outlet of the ozone generator was controlled to be 1 L / min, the O3 gas concentration was 10 mg / L, and the COD concentration change was analyzed by sampling after 60 minutes of reaction. The treatment results are shown in Table 2.
[0029] Table 1
[0030] Example 2 The method is the same as that of Example 1, except that when preparing the spherical catalyst, the calcination temperature is 500-600°C.
[0031] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0032] Example 3 The method is the same as that of Example 1, except that when preparing the spherical catalyst, the calcination temperature is 600-800°C.
[0033] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0034] Example 4 The method is the same as that in Example 1, except that when preparing the spherical catalyst, the calcination temperature is 800-1000°C.
[0035] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0036] Example 5 The method is the same as that of Example 1, except that when preparing the spherical catalyst, the calcination time is 2 hours.
[0037] The catalytic performance test of the catalyst prepared in this example is shown in Table 6.
[0038] Example 6 The same as Example 1, except that when preparing the spherical catalyst, the calcination time is 3 hours.
[0039] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0040] Example 7 The same as Example 1, except that when preparing the spherical catalyst, the calcination time is 5 hours.
[0041] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0042] Example 8 The method is the same as that of Example 1, except that the total loading amount of Mn, Fe, Ti, and Al oxides is 3-8%.
[0043] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0044] Example 9 The method is the same as that of Example 1, except that the total loading of Mn, Fe, Ti, and Al oxides is 8-16%.
[0045] The catalytic performance test of the catalyst prepared in this example is shown in Table 2.
[0046] Comparative Example 1 The method is the same as that of Example 1, except that the composite catalyst prepared by the present invention is not added into the reaction system.
[0047] The catalytic performance test of the catalyst prepared in Comparative Example 1 is shown in Table 2.
[0048] Comparative Example 2 The method is the same as that in Example 1, except that the surface of the ceramsite carrier is not loaded with active Mn, Fe, Ti, and Al oxide components.
[0049] The catalytic performance test of the catalyst prepared in Comparative Example 2 is shown in Table 2.
[0050] Comparative Example 3 The method is the same as that of Example 1, except that no active Mn oxide component is loaded on the catalyst surface.
[0051] The catalytic performance test of the catalyst prepared in Comparative Example 3 is shown in Table 2.
[0052] Comparative Example 4 The method is the same as that of Example 1, except that the active Fe oxide component is not loaded on the catalyst surface.
[0053] The catalytic performance test of the catalyst prepared in Comparative Example 4 is shown in Table 2.
[0054] Comparative Example 5 The method is the same as that of Example 1, except that no active Ti oxide component is loaded on the catalyst surface.
[0055] The catalytic performance test of the catalyst prepared in Comparative Example 5 is shown in Table 2.
[0056] Comparative Example 6 The method is the same as that of Example 1, except that the active Al oxide component is not loaded on the catalyst surface.
[0057] The catalytic performance test of the catalyst prepared in Comparative Example 6 is shown in Table 2.
[0058] Table 2
[0059] In a second aspect, an application of an ozone catalytic oxidation composite catalyst is provided. Based on the preparation method of the ozone catalytic oxidation composite catalyst described in the first aspect, the MFTA@ceramsite ozone catalyst is applied to water treatment. Beneficial Effects
[0060] 1. The present invention uses ceramsite as a carrier, which is simple to prepare, low in price, and has a stable structure, which is conducive to the uniform loading of active components and improves the rate of catalytic oxidation reaction.
[0061] 2. The present invention adopts a spherical granulation method to prepare ceramsite-loaded Fe, Mn, Al, and Ti catalysts. The active components are firmly loaded, evenly distributed, and highly dispersed. In addition, the preparation process is simple, highly repeatable, and has low energy consumption.
[0062] 3. The selected carriers and active components are common commercially available materials with low preparation costs.
[0063] 4. The catalyst prepared by the present invention can generate more hydroxyl radicals, improve the oxidation efficiency and utilization rate of ozone, greatly improve the catalytic oxidation efficiency of difficult-to-degrade organic matter, which is more than 45% higher than that of ozone oxidation alone, saving operating costs.
[0064] 5. The catalyst prepared by the present invention has been repeatedly used and found that the active components are firmly attached and not easily lost, thus avoiding secondary pollution during the catalytic oxidation process.
[0065] The above disclosure is only a preferred embodiment of the preparation method and application of an ozone catalytic oxidation composite catalyst of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing an ozone catalytic oxidation composite catalyst, characterized in that: The following steps are involved: Using clay and MnSO4 solution to prepare ceramsite; The composite powder catalyst was prepared by coprecipitation-oxidation-reduction method; The ceramsite and the composite powder catalyst are mixed and calcined to obtain the MFTA@ceramsite ozone catalyst.
2. The method for preparing the ozone catalytic oxidation composite catalyst according to claim 1, characterized in that: In "Preparing ceramsite using clay and MnSO4 solution", the MnSO4 is a 0.01-0.5MMnSO4 solution, and the particle size of the ceramsite is 5-7mm.
3. The method for preparing the ozone catalytic oxidation composite catalyst according to claim 1, characterized in that: In "Preparation of composite powder catalyst by coprecipitation-redox method", the composite powder catalyst is composed of at least two (MFTA) of four metal oxides of Mn, Fe, Ti and Al.
4. The method for preparing the ozone catalytic oxidation composite catalyst according to claim 4, characterized in that: In "Preparing a composite powder catalyst by a coprecipitation-oxidation-reduction method", the following steps are included: The Mn component in the MFTA catalyst was prepared by a redox method; KMnO4 solution was dripped into MnSO4 solution at 60-90°C, and after the dripping was completed, the reaction was continued for 6-12 hours and the aging was continued for 6-8 hours; Dissolve TiOSO4·H2SO4·H2O in water, stir the solution until it becomes colorless and transparent, then add Fe(NO3)3·9H2O and Al(NO3)3·9H2O in sequence, continue stirring for 2-4 hours, then add the Mn component prepared by the redox method, stir evenly, slowly drop NaOH to adjust the pH to neutral, continue stirring for 6-8 hours after the pH value stabilizes, and stand at 60-90°C for aging to obtain a solid precipitate; The solid precipitate was washed with water, filtered and dried in an oven for 12 hours to obtain a composite catalyst, which was then ground into powder.
5. The method for preparing the ozone catalytic oxidation composite catalyst according to claim 1, characterized in that: In “mixing ceramsite and a composite powder catalyst and then calcining to obtain a MFTA@ceramsite ozone catalyst”, the mixing ratio of the composite powder catalyst and the ceramsite is 8-10:
1.
6. An application of an ozone catalytic oxidation composite catalyst, based on the preparation method of the ozone catalytic oxidation composite catalyst according to any one of claims 1 to 5, characterized in that: MFTA@ceramsite ozone catalyst is used in water treatment.
Citation Information
Cited By
High-strength multi-element iron-based ozone catalyst, preparation method thereof and application of high-strength multi-element iron-based ozone catalyst in catalytic degradation of DMP
CN122377469A